STUDENT'S PERCEPTION ON THE SECOND LANGUAGE ACQUISITION (SLA COURSE) THROGH GOOGLE CLASSROOM - Wihastyanang, Wardani Dwi; Perdana, Indra; MARHABAN, SAIFUL (English Teaching Journal : A Journal of English Literature, Language and Education, 2023)
The researcher was intended to meet the following objectives to know the student's perception regarding Google Classroom and Google form implementation on Second Language Acquisition online learning. Meanwhile, in this study the researchers made changes to the needs of students in using the google classroom application during the Covid-19 pandemic with the subject of the Second Language Acquisition Course using the questionnaire method. This study wil use qualitative through, it was given to both teachers and students to know their experiences. The survey used online questionaire which was adapted from Asnawi (2018), then the descriptive method used to describe the condition of existence and classifying the information. The respondents of this research is students of English Department of UNIVERSITAS PGRI JOMBANG. They were 39 respondents. The result of this study discovered learners' perception of learning using the online media during COVID 19 pandemic. Findings indicated general satisfactory among learners regarding instructional design and delivery of online learning including the provision of materials, supporting learning materials and instructions to tasks submission. Students felt the need for improvement in designing activities to engage their critical thinking. Formative assessment must also be provided timely through each courses. Teachers along with policy makers of the institution have to reshape the dynamic of online learning delivery in order to create greater participation and engagement between students, not only in independent tasks but also tasks that involve group work.